(untitled) (Research, Society and Development, 2022)
This article aims to demonstrate the necessity and possibility, legal and administrative feasibility of implementation supervised training and procedural administrative practice center within the Military Police of the State of Tocantins in the course of training for officers, through an act of the Chief Executive Power for the creation of said center, regulated by the command of the institution and change in the CFO Political Pedagogical Project. Consists of relevant and enlightening chapters, focusing on the theme of education on the corporation, taking into account the relevant concepts, the history of the Military Police of the State of Tocantins and practice of teaching in the Corporation, advances made to the practice of teaching, research by the Internal Affairs Division, finding mistakes to be corrected and the presentation of possible solutions. Thus, the work configures itself as study and at the same time, presents viable proposals for educational and professional development in the institution and therefore the possibility of better qualification of its members, strengthening the actions of the internal affairs, as a result, responsables and military polices scribes will be better prepared, resulting in better service delivery to the Tocantins society.